Control charts for monitoring multi-stage service processes with optimal queue performance. Issue 9 (1st September 2020) - Ebadi, Mohsen; Ahmadi-Javid, Amir
Abstract: This paper develops control charts for monitoring the service times at the different stages of a congested system that provides a multi-stage service to its customers. A simulation-based optimization procedure is used to simulate the whole service process and determine the chart parameters that minimize the average time a customer spends in the system. Statistical constraints are also considered to enhance the statistical properties of the control chart. The proposed socio-statistical method may be of interest for a variety of applications. The method is applied to a fast food restaurant with two waiting stages.